Study of Dielectric and Adsorption Properties of Activated Carbon Prepared from Water Hyacinth using KOH as an Activating Agent - Ghiffari, Mochammad; Maulina, Wenny; Nugroho, Agung Tjahjo (Computational And Experimental Research In Materials And Renewable Energy, 2020)
Activated carbon can be produced from the combustion of a materials containing carbon that has been activated using activator substances. In this paper, potassium hydroxide (KOH) was selected as an activating agent. The influence of KOH concentration was investigated to determine the dielectric and adsorption properties of activated carbon derived from water hyacinth. Drying water hyacinth was carbonize in the furnace at a temperature of 400°C followed by chemical activation with variation concentration of KOH solution that used are 25%, 30%, and 35% (w/v) respectively. The results show that the best activated carbon derived from water hyacinth was obtained using 35% (w/v) KOH solution as an activating agent with the dielectric constant is 4,04 while iodine number of 514,6 mg/g.